Features of the physique in young martial arts athletes - S.S. Bovykin; E.Z. Godina; I.A. Khomyakova (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the features of the physique of young martial arts athletes aged 9-13 years. Methods and structure of the study. The somatic features (more than 30 signs and indices characterizing the size and proportions of the body) of boys aged 9 to 13 years were studied. At each age, two groups were compared: athletes specializing in various types of wrestling (surveyed in 2018), and a control group of schoolchildren not involved in sports (surveyed in 2013-2017). The total number of subjects was 686 people. Results and conclusions. The features of body proportions in young wrestlers are revealed: absolutely and relatively wide shoulders, absolutely and relatively elongated torso. Athletes are distinguished by an increased development of chest and forearm girths; schoolchildren who do not play sports have larger waist, buttocks, shoulders and hips. The development of subcutaneous fat deposition in two samples does not fully correspond to the circumference dimensions: the thickness of the skin-fat fold over the triceps and on the abdomen (straight line) is greater in athletes. At the same time, the thickness of the skin-fat fold on the forearm of martial artists is less than that of boys from the control group. Such a combination of somatic characteristics in martial artists specializing in different types of wrestling is considered as a wrestling body type. A comparative analysis of martial arts athletes and schoolchildren who are not involved in sports revealed the most informative signs in relation to sports selection (ratio of skeletal dimensions) and the level of physical activity and their specificity (circumference dimensions of the body and subcutaneous fat deposition). Growth processes at all stages of ontogenesis significantly correct the morphological features of athletes in different sports.